Neutrophil gelatinase-associated lipocalin as a potential therapeutic integrator of glycolipid metabolic and inflammatory signaling - Gong, Junhua; Zhu, Rongtao; Gong, Jianping; He, Kun; Chen, Jiahai (International Surgery Journal, 2017)
Metabolic syndrome constitutes a group of metabolic conditions that increase the risk of developing diseases, including cardiovascular disease (CVD), non-alcoholic fatty liver disease (NAFLD), obesity and type 2 diabetes mellitus (T2DM) etc. Subclinical inflammation is a candidate etiological factor in the pathogenesis of metabolic syndrome and in the progression of related diseases. Although studies have revealed that subclinical inflammation was activated by intermediary products of basic metabolic processes, the cellular and molecular mechanisms in this association remain largely uncharacterized. Recently, increasing evidence suggests that neutrophil gelatinase-associated lipocalin (NGAL) not only plays a significant role in the glycolipid metabolism, but also modulates immune and inflammatory responses in macrophages. Taking together the ability of NGAL in metabolic and inflammatory signaling, these data suggest that NGAL may be a potential therapeutic target for metabolic and inflammatory signaling for intervention in human glycolipid metabolic disease. This review focuses on current knowledge of the integrators role of NGAL in both glucose and lipid metabolism and inflammatory signaling and discusses the potential therapeutic target in the treatment of glycolipid metabolic-related disease.